PENGARUH MASA PENUGASAN DAN UKURAN KANTOR AKUNTAN PUBLIK PADA KUALITAS AUDIT (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2007-2011) - , AGNES JESICA ULIARTHA, Gunawan Wibisono, S.E., M.Acc ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Auditors play a role in preventing the occurrence of moral hazard in the financial statements of the company. When performing their duties, auditor must maintain independence in order to produce a quality audit. Two factors that may affect the independence of the auditor are audit tenure and the size of public accounting firm. Several previous researches that examined these factors showed different results. The purpose of this research is to demonstrate empirically the relation of audit tenure and the size of public accounting firm upon audit quality. Audit quality is measured using the earnings surprise benchmark, a way of measuring that connecting audit quality with managerâs tendency in doing earnings management. The population of this research is manufacturing companies listed in Indonesia Stock Exhange (BEI) for the period of 2007-2011. By using purposive sampling, 113 manufacturing companies obtained as the research samples. The hypothesis testing was conducted using logistic regression analysis in SPSS 19.0 for Windows. The result of this research has showed that audit tenure has a positive and significant impact on audit quality, while the size of public accounting firm has a negative and significant impact on audit quality